Diameter-sensitive biocompatibility of anodic TiO(2) nanotubes treated with supercritical CO(2) fluid - Lan, Ming-Ying (Springer, 2013)
This work reports on the diameter-sensitive biocompatibility of anodic TiO(2) nanotubes with different nanotube diameters grown by a self-ordering process and subsequently treated with supercritical CO(2) (ScCO(2)) fluid. We find that highly hydrophilic as-grown TiO(2) nanotubes become hydrophobic after the ScCO(2) treatment but can effectively recover their surface wettability under UV light irradiation as a result of photo-oxidation of C-H functional groups formed on the nanotube surface. It is demonstrated that human fibroblast cells show more obvious diameter-specific behavior on the ScCO(2)-treated TiO(2) nanotubes than on the as-grown ones in the range of diameters of 15 to 100 nm. This result can be attributed to the removal of disordered Ti(OH)(4) precipitates from the nanotube surface by the ScCO(2) fluid, thus resulting in purer nanotube topography and stronger diameter dependence of cell activity. Furthermore, for the smallest diameter of 15 nm, ScCO(2)-treated TiO(2) nanotubes reveal higher biocompatibility than the as-grown sample.